Estudo de caso sobre a evasão em um curso de Teologia a distância - Monteiro, Enilson Elias de Castro (2016)
This research dissertation is titled Case Study About Evasion in a Distance Learning Theology Course. The work is within the concentration area of Cognitive Processes and Digital Environments aligned with the research field of Learning and Cognitive Semiotics from the Stricto Sensu Graduate Program of Intelligence and Digital Design Technologies. The study aims to answer a guiding question about what are the reasons that led students to evade from the Distance Learning Free Theology Course of Latin American Faculty (FLAM). The objective of the research is to investigate the dropout phenomenon in the Distance Learning Free Theology Course offered by FLAM, analyzing it by the theory of transactional distance. For this, it commits to investigate the perceptions of evaded students and their course tutors about the teaching and learning process of this specific course as long as the possible causes of evasion; examine these reasons, categorizing them according to the variables dialogue, structure and autonomy, as presented in Theory of Transactional Distance and propose possible interventions that may reduce the evasion rates of the course. The research methodology is based on a qualitative approach, searching not only to pull up data but also to interpret and give them meaning in their own context. About the dissertation work type, it is a case study. As an instrument for data collection it was used the application of an online questionnaire to alumni and semi-structured interviews with two tutors of the course. For data analysis, this work employees the methodology of thematic analysis of content. The research result ends up denying the initial hypotheses to conclude that dropout reasons external to the course were a major factor than internal reasons and thus the phenomena is not related to the variables of transactional distance